2022
DOI: 10.1021/acsapm.1c01788
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Network Hierarchically Organized on Carbon Nano-onions: Block Polymerization as a Tool for the Controlled Formation of Specific Pore Diameters

Abstract: The organization of specific pores in carbonaceous three-dimensional networks is crucial for efficient electrocatalytic processes and electrochemical performance. Therefore, the synthesis of porous materials with ordered and well-defined pores is required in this field. The incorporation of carbon nanostructures into polymers can create material structures that are more ordered in comparison to those of the pristine polymers. In this study we applied polymer-templated methods of carbon material preparation, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…7 Moreover, combining faradaic and non-faradaic processes in SCs can achieve higher energy and power density while maintaining long-term electrochemical stability. Our studies show that using CNOs during the synthesis of macromolecular systems may organize the organic framework of oligomers, 8 polymers 9,10 or CTFs 5 and alter the uniform distribution of pores and pore sizes (micropores (<2 nm), mesopores (2–50 nm) and macropores (>50 nm)) within the materials. Additionally, the combination of two components also guarantees an increase in the total porosity of the material, which is critical when using them as electrodes in SCs.…”
Section: Introductionmentioning
confidence: 89%
“…7 Moreover, combining faradaic and non-faradaic processes in SCs can achieve higher energy and power density while maintaining long-term electrochemical stability. Our studies show that using CNOs during the synthesis of macromolecular systems may organize the organic framework of oligomers, 8 polymers 9,10 or CTFs 5 and alter the uniform distribution of pores and pore sizes (micropores (<2 nm), mesopores (2–50 nm) and macropores (>50 nm)) within the materials. Additionally, the combination of two components also guarantees an increase in the total porosity of the material, which is critical when using them as electrodes in SCs.…”
Section: Introductionmentioning
confidence: 89%
“…The hierarchical distribution of CN, in the amount of only ca. 5%, in a porous carbon matrix was responsible for increasing of the porosity and C S value compared to pristine pyrolyzed polymers 54 .…”
Section: Introductionmentioning
confidence: 91%
“…However, the range of CNO content was high, equal to 5–75 wt%, in the starting synthesized gels before the thermal treatments. Furthermore, our group developed polymer-templated carbon materials derived from star-block copolymers and CNOs 54 , 55 . The hierarchical distribution of CN, in the amount of only ca.…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial discovery of CNOs, many attempts have been made to identify the reaction conditions that yield high-purity CNOs in large quantities. These attempts have employed numerous methods using various raw-carbon precursors to synthesize CNOs, including annealing, [191] arc discharge, [192] gas-liquid detonation, [193] electrochemical, [194] CVD, [195] ambient electrospray deposition, [196] and plasma-spray from NDs. [197,198] However, our thorough analysis of the literature revealed that amongst these methods, only a few techniques have occupied the main streams of current research due to their substantial potential in producing significant quantities of CNOs that might meet the stringent demands of commercial production.…”
Section: Synthesis and Fabrication Of Carbon Nanoonionsmentioning
confidence: 99%